THE GREEN PURCHASE GAP IN E-COMMERCE: THE ROLE OF PRICE SENSITIVITY AND PERCEIVED BEHAVIORAL CONTROL - Lukito Angga Prasakti; Asep Koswara; Tarso; Herman Soegoto; Lilis Puspitawati (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2026)
The growing demand for environmentally friendly products has not always been accompanied by actual purchasing behavior, resulting in a phenomenon known as the green purchase gap. This study investigates the effects of Price Sensitivity and Perceived Behavioral Control on the Green Purchase Gap among consumers of green products in e-commerce. Drawing on the Theory of Planned Behavior and economic decision-making perspectives, this research examines why consumers fail to translate pro-environmental intentions into actual purchases. A quantitative approach was employed using survey data collected from 120 respondents, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that Price Sensitivity has a significant positive effect on the Green Purchase Gap, whereas Perceived Behavioral Control has no significant effect. These findings suggest that consumers’ economic evaluations play a more important role than perceived capability in determining actual green purchasing behavior. The study contributes to the literature by highlighting the importance of integrating psychological and economic perspectives in explaining the intention–behavior gap. Practically, the findings imply that reducing price-related barriers may be more effective than solely increasing consumers’ awareness or perceived control in promoting sustainable consumption.